ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN PADA USAHA BUNGA PAPAN ANISYAH RASYID FLORIST - Hendra Musa (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
Business strategy in digital era is refers to consumer satisfaction that should be a concern for companies to attempt in business. Consumer satisfaction is determined by the quality of service provided by the company in order with consumer expectations. Consumer satisfaction is the expectation and performance carried out on demand. Consumer satisfaction means that the company's performance is the same as with the expected by consumers. One effort that can be done by companies to find out the services provided is by analyzing the level of consumer satisfaction. Consumer satisfaction is a measure of the company's success in providing services. The implementation of marketing products and services is inseparable from the satisfaction of consumers / customers. The measurement process starts from determining who will be served, then monitored from the desired quality level and made a marketing strategy. This research was conducted at the Anisyah Rasyid Florist, with the object of research in Anisyah Rasyid Florist consumers. The method used is interview, observation, and questionnaire. Analysis data used the descriptive quantitative analysis, using the equation method: IKP = PP-EX, respondent characteristics and analysis of the consumer level suitability that is by comparing the level of consumer expectations with the level of real performance on Anisyah Rasyid Florist. The results, that all service quality indicators get positive scores. All respondents showed great expectations for all indicators used in measuring the quality of services provided. The conclusion is from the nine indicators of consumer service quality used the level of satisfaction is good.